Using the transformation T: (x, y) (x + 2, y + 1), find the distance named. Find the distance BB'

Answers

Answer 1
Answer:

Answer:

√(5)\ units


Step-by-step explanation:

we know that

The rule of the translation is equal to

(x,y)-----> (x+2,y+1)

That means

The translations is 2 units to the right and 1 unit up

Let

(x,y)-------> the coordinates of point B

(x+2,y+1)------> the coordinates of point B'

Find the distance

the formula to calculate the distance between two points is equal to


d=\sqrt{(y2-y1)^(2)+(x2-x1)^(2)}


substitute

d=\sqrt{((y+1)-y)^(2)+((x+2)-x)^(2)}


d=\sqrt{(1)^(2)+(2)^(2)}


d=√(5)\ units


Answer 2
Answer: The transformation is:
T : ( x , y ) → ( x + 2, y + 1 )
B ( 1, 3 ) → B` ( 1 + 2, 3 + 1 )
B ` ( 3, 4 )
d ( B B`) = √(( 3 - 1 )² + ( 4 - 3 )² )=
=  √ (2² + 1²) = √ 5

Related Questions

Is y=1/4x^0.5 a power function? Explain your reasoning.
Please help need in next 10 minutesOn your property tax bill, you see the following table. Destination Share of Your Taxes Roads $241 Schools $896 Public Safety $154 Township $177 What percentage of your taxes went to funding public safety? a. 10.49% b. 12.06% c. 11.72% d. 8.94%
Write an equation of the line passing through points (3,8) and (-2,-22)
I NEED HELP WITH THIS PLS Q1
Solving equations. find value of m2m - 1/2 = m/7 + m/2here is a picture of the previous question

Henry is four times older than James. Next year, Henry will be three times older than James will be. How old are Henry and James now?
a. James is 3 years old; Henry is 4 years old.
b. Henry is 4 years old; James is 3 years old.
c. James is 2 years old; Henry is 8 years old.
d. James is 8 years old; Henry is 8 years old.

Answers

The answer would be C. James is 2, Henry is 8.
This year, Henry is 4 times older than James. (2×4=8)
Next year, Henry will be 3 times older than James. (3×3=9)

Bryan’s monthly electric bill is determined by adding a flat administration fee to the product of the number of kilowatt hours of electricity used and the cost per kilowatt hour. When he uses 1,100 kilowatt hours of electricity, his bill is $113. When he uses 1,500 kilowatt hours of electricity, his bill is $153. What is the monthly administration fee?

Answers

We will form the equations for this problem:
(1) 1100*y + z = 113
(2) 1500*y + z = 153
z = ? Monthly administration fee is notated with z, and that is the this problem's question.
Number of kilowatt hours of electricity used are numbers 1100 and 1500 respectively.
Cost per kilowatt hour is notated with y, but its value is not asked in this math problem, but we can calculate it anyway.
The problem becomes two equations with two unknowns, it is a system, and can be solved with method of replacement:
(1) 1100*y + z = 113
(2) 1500*y + z = 153
----------------------------
(1) z = 113 - 1100*y [insert value of z (right side) into (2) equation instead of z]:
(2) 1500*y + (113 - 1100*y) = 153
-------------------------------------------------
(1) z = 113 - 1100*y
(2) 1500*y + 113 - 1100*y = 153
------------------------------------------------
(1) z = 113 - 1100*y
(2) 400*y + 113 = 153
------------------------------------------------
(1) z = 113 - 1100*y
(2) 400*y = 153 - 113
------------------------------------------------
(1) z = 113 - 1100*y
(2) 400*y = 40
------------------------------------------------
(1) z = 113 - 1100*y
(2) y = 40/400
------------------------------------------------
(1) z = 113 - 1100*y
(2) y = 1/10
------------------------------------------------
if we insert the obtained value of y into (1) equation, we get the value of z:
(1) z = 113 - 1100*(1/10)
(1) z = 113 - 110
(1) z = 3 dollars is the monthly fee.

Answer:

3

Step-by-step explanation:

correct on ed (:

Solve rational inequality x²+x-6/x²-3x-4≤0?​

Answers

Applying division signal rules, from the graphs of both functions, it is found that the solution of the inequality is:

x \in [-3,-1) \cup [2,4)

------------------

A fraction, which represents a division, is negative if the numerator and the denominator have different signals. Thus, to solve this inequality, we have to study the signals of the numerator and the denominator.

The numerator is: f(x) = x^2 + x - 6

  • It is the first graph appended at the end of this answer.
  • From the graph, we have that it is negative or zero on [-3,2], and positive on the rest of the interval.

The denominator is: g(x) = x^2 - 3x - 4

  • It is the second graph appended at the end of this answer.
  • The denominator cannot be zero, so we consider only the interval (-1,4), in which it is negative.

  • Numerator positive, denominator negative: On interval [2,4).
  • Denominator positive, numerator negative. On interval [-3,-1).

Thus, the solution is:

x \in [-3,-1) \cup [2,4)

A similar problem is given at brainly.com/question/14361489

Answer:

x ∈ [-3;-1) ∪ [2;4)

Step-by-step explanation:

(x^(2)+x-6 )/(x^(2)-3x-4 )\leq 0\n=> ((x-2)(x+3))/((x+1)(x-4)) \leq 0\n

we have this board:

x                          -3                    -1                      2                     4          

x - 2          -                        -                    -           0        +                     +

x+3            -         0           +                   +                      +                     +

x+1             -                      -            0      +                      +                     +

x-4            -                        -                     -                     -            0      +

((x-2)(x+3))/((x+1)(x-4))   +          0          -             ||        +         0        -            ||        +

from the board

=>    x ∈ [-3;-1) ∪ [2;4)

I got 60 right out of 110 questions on a test. What was my overall grade/percentage?

Answers

What you do is you make it into a fraction. You got 60 out of 110, so that's 60/110. Because all fractions are practically division problems, that's 60 ÷ 110 = 0.5454545454...
Times that by 100 to get the percentage.
Ans-YOUR OVERALL PERCENTAGE IS 54%

Multiply. Write your answer in simplest form.

5/12 x 4/5

Answers

(5)/(12) * (4)/(5)
The fives cancel each other and the four goes into the twelve and leaves 3
(1)/(3) * (1)/(1) = (1)/(3)

Which of the number(s) below are potential roots of the function?p(x) = x4 + 22x2 – 16x – 12

Answers

Potential\ roots\ of\ the\ function:\n\np(x)=x^4+22x^2-16x-12\ are:\n\n\{\pm1;\pm2;\pm3;\pm4;\pm6;\pm12\}

Answer:

6,1,3

Step-by-step explanation: